Isolation and Characterization of Exopolysaccharide-Producing Lactobacillus plantarum SKT109 from Tibet Kefir - Wang Ji; Zhao Xiao; Tian Zheng; He Congcong; Yang Yawei; Yang Zhennai (Polish Journal of Food and Nutrition Sciences)
Lactobacillus plantarum SKT109 was isolated and identified from Tibet Kefir, and the exopolysaccharride (EPS)-producing properties of the strain were evaluated. Growth of strain SKT109 in a semi-defined medium at 37°C increased the viscosity of the medium, corresponding to production of an EPS (58.66 mg/L). The EPS was isolated and purified, and it was shown to consist of fructose and glucose in an approximate molar ratio of 3:1, with an average molecular weight of 2.1×106 Da. The aqueous solution of EPS at 1% (w/v) exhibited shear thinning behavior. Microstructural studies of the EPS demonstrated a highly compact structure with a smooth surface, facilitating formation of film by the polymer; the EPS was composed of many different sizes of spherical lumps with tendency to form molecular aggregates. Studies on the milk fermentation characteristics of L. plantarum SKT109 showed that the strain survived well in fermented milk with counts about 8.0 log cfu/g during 21 days of storage at 4°C. The use of the EPS-producing strain improved the rheology of the fermented milk without causing post-acidification during storage. Particularly, L. plantarum SKT109 improved the fermented milk flavor by increasing the concentration of characteristic flavor compounds and eliminating those with dis gusting flavors. The results of the present study indicated that EPS-producing L. plantarum SKT109 could serve as a promising candidate for further exploitation in fermented foods.